2018
DOI: 10.1177/1359105317748734
|View full text |Cite
|
Sign up to set email alerts
|

The effect of body dissatisfaction on disordered eating: The mediating role of self-esteem and negative affect in male and female adolescents

Abstract: This study aimed to determine whether self-esteem and negative affect sequentially mediate the relationship between body dissatisfaction and disordered eating. A total of 806 adolescents (61.8% females) completed the Drive for Thinness, Bulimia, and Body Dissatisfaction subscales of the Eating Disorder Inventory-2, the Anxiety and Depression subscales of the General Health Questionnaire-28, and the Negative Self-beliefs subscale of the Eating Disorder Belief Questionnaire. Mediational analyses showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 43 publications
(72 reference statements)
4
38
0
1
Order By: Relevance
“…These results confirm that social affiliation promotes positive feelings and healthy life styles [24]. Although previous studies have interpreted social recognition as an extrinsic goal, this study only found a significant effect of dissatisfaction with body image on developing eating disorders and unhealthy eating styles [16,40].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results confirm that social affiliation promotes positive feelings and healthy life styles [24]. Although previous studies have interpreted social recognition as an extrinsic goal, this study only found a significant effect of dissatisfaction with body image on developing eating disorders and unhealthy eating styles [16,40].…”
Section: Discussionsupporting
confidence: 83%
“…High levels of self-esteem are also related to optimum academic performance [9], higher job performance and commitment [10,11], and it is an important protection factor against burnout in healthcare professionals [12]. On the contrary, low levels of self-esteem have been associated with depressive symptoms [13], anxiety [14], suicidal ideation [15], eating disorders [16] and violent behavior [17]. In brief, our overall self-assessment determines the way we are, the way we perceive the world and relate with others, and therefore, influences our success in important facets of life [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the negative correlation found between weight and Global self-esteem is in accordance with other researches [ 63 , 64 ], in fact, being overweight was associated with lower self-esteem. For this reason, self-esteem could be considered a mediating factor for a greater or lower risk of eating disorder, which has been explored by other authors [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, a recently published eye-tracking study (Svaldi et al, 2016) found that women with AN (n = 12) display a greater attentional negativity bias during a 3-minute mirror exposure-with higher gaze frequency and duration toward disliked than liked body parts-in response to an induction of negative relative to positive mood. Nevertheless, emotional events have been shown to trigger binge eating in patients with BN and binge eating disorder (BED) (Berg et al, 2017;Lavender et al, 2016;Svaldi, Werle, Naumann, Eichler, & Berking, 2019), and there is correlational evidence that negative affect mediates the relationship between body dissatisfaction and bulimic-eating behavior (Cruz-Saez, Pascual, Wlodarczyk, & Echeburua, 2018). Nevertheless, emotional events have been shown to trigger binge eating in patients with BN and binge eating disorder (BED) (Berg et al, 2017;Lavender et al, 2016;Svaldi, Werle, Naumann, Eichler, & Berking, 2019), and there is correlational evidence that negative affect mediates the relationship between body dissatisfaction and bulimic-eating behavior (Cruz-Saez, Pascual, Wlodarczyk, & Echeburua, 2018).…”
mentioning
confidence: 99%
“…In BN, however, no reports on the influence of emotions on attentional processing during mirror exposure have been published yet. Nevertheless, emotional events have been shown to trigger binge eating in patients with BN and binge eating disorder (BED) (Berg et al, 2017;Lavender et al, 2016;Svaldi, Werle, Naumann, Eichler, & Berking, 2019), and there is correlational evidence that negative affect mediates the relationship between body dissatisfaction and bulimic-eating behavior (Cruz-Saez, Pascual, Wlodarczyk, & Echeburua, 2018). Furthermore, results from an older experimental study suggest that the induction of low mood leads to feelings of being larger in women with BN relative to a non-emotional condition (Carter, Bulik, Lawson, Sullivan, & Wilson, 1996).…”
mentioning
confidence: 99%